2022
DOI: 10.3390/ijerph19074002
|View full text |Cite
|
Sign up to set email alerts
|

Severity Analysis of Hazardous Material Road Transportation Crashes with a Bayesian Network Using Highway Safety Information System Data

Abstract: Although crashes involving hazardous materials (HAZMAT) are rare events compared with other types of traffic crashes, they often cause tremendous loss of life and property, as well as severe hazards to the environment and public safety. Using five-year (2013–2017) crash data (N = 1610) from the Highway Safety Information System database, a two-step machine learning-based approach was proposed to investigate and quantify the statistical relationship between three HAZMAT crash severity outcomes (fatal and severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Random Forest is used to predict classification and regression situations on large datasets. This approach involves combining results from each decision tree for classification as well as averaging the regression results [10], [18].…”
Section: B Random Forestmentioning
confidence: 99%
“…Random Forest is used to predict classification and regression situations on large datasets. This approach involves combining results from each decision tree for classification as well as averaging the regression results [10], [18].…”
Section: B Random Forestmentioning
confidence: 99%
“…However, they usually require certain assumptions in the crash data, and it is challenging to discover the underlying crash patterns and the interaction among various variables. Data mining and machine learning approaches for truck-related crash data processing and analysis, including classification trees [23], taxicab correspondence analysis [24], association rules mining [25], and Bayesian networks [26][27][28], have become increasingly popular in recent years. For example, Das et al [24] utilized taxicab correspondence analysis to uncover the complex interactions between multiple risk factors and large truck-involved fatal crashes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to their findings, the most important attributes were packing and loading of HAZMAT, vehicle and facility-related factors, and human factors. Similarly, Ma et al [27] also utilized Bayesian networks to explore the most probable factors or the combination of factors leading to the crash-a recent HAZMAT crash severity prediction study [28] combined random forest and Bayesian networks. Random forest ranked the importance of risk factors, and Bayesian networks developed the probabilistic inference.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, most scholars combine other methods to preprocess the data before modeling to efectively improve model accuracy. Hashemi et al [10] proposed a multivariate security analysis model based on copula BN, combined with the copula function to consider the correlation between variables, and illustrated the superior performance of the CBN model compared to the traditional BN model through a case; Huang et al [11] combined the explanatory structural model (ISM) and the BN model to construct a BN model for predicting hazardous materials road transport accidents after identifying causal relationships between variables; Sun et al [12] used random forests to rank the importance of risk factors for hazardous materials transport and then developed a BN to provide probabilistic inference, and the results showed that the proposed method was very efcient; Shen et al [13] used fault tree analysis to frst fnd the direct and indirect causes of hazardous transport accidents and constructed a BN model with strong descriptive power; Ding et al [14] combined the credal network and IDM methods to construct a model for analyzing the causes of hazardous materials road transport accidents based on a credal network; Pan et al [15] proposed a risk assessment method based on an improved FBN model, which provides an efective tool for risk management of hazardous material transportation enterprises; Wang et al [16] frst used the grounded theory (GT) to identify infuencing factors and then developed a BN-based model for these collected hazardous materials transport accidents; and Cheng et al [17] used dynamic BN to calculate the likelihood of hazardous chemical spills and explosions. In conclusion, it can be seen that before constructing the BN model, it is important to efectively deal with the relationship among the factors afecting hazardous materials road transport accidents to improve the accuracy and robustness of the model.…”
Section: Introductionmentioning
confidence: 99%